Designing a Strategic Renewal Model for Development of Organizations in Iran based on the Professional Identity of Managers (Case Study: The State-owned Companies of IDRO) - Mahdieh Vishlaghi; Alireza Moghaddam; Reza Sepahvand; adel azar (‫مدیریت بازرگانی, 2022)
Objective Dealing with internal and external changes and complexities, requires the ability of organizations to create and reconfigure their capabilities. In this regard, strategic renewal, which seeks to coordinate and adapt internal and external capabilities, requires managers with new professional identities who are compatible with the new direction of the organization. The present study aimed to design a strategic renewal model based on the professional identity of managers of development organizations in Iran.